Study of the transit and attenuation of pollutants in a water reservoir receiving acid mine drainage in the Iberian Pyrite Belt (SW Spain) - Santisteban, M. (2016)
The Sancho Dam was built in 1962 and is fed by the Meca River, which receives water from subsidiary tributaries affected by acid mine drainage (AMD), mostly generated by the abandoned Tharsis mining complex. This study focuses on the hydrochemical relations observed between the water at the entrance of the reservoir and a point located further away, specifically at the dam. The main aim is to analyze the water parameters in both monitored points, in order to evaluate possible attenuation processes and to propose a spatial evolution model of the pollutants' load by using cross-correlation functions. Concentrations of metals and sulfates put in evidence their contamination by acid mine drainage, with greater pollution load at the entrance of the reservoir than in the dam, due to the reduction of the same in the course between the two points. This attenuation results from the precipitation of iron oxyhydroxysulfates produced by the increase in the pH as well as by dilution and sorption phenomena. The cross-correlation functions show the close relationship between the two sampling points with a transit time of contaminants less than 1 week (t = 0) for most cases, due to the small distance between the two points (about 300 meters).